Latência e amplitude do P300 auditivo na doença de Alzheimer: uma revisão sistemática - Pedroso, Renata Valle [UNESP]; Fraga, Francisco J.; Corazza, Danilla Icassatti [UNESP]; Andreatto, Carla Andrezza Almeida [UNESP]; Coelho, Flávia Gomes de Melo [UNESP]; Costa, José Luiz Riani [UNESP]; Santos-Galduróz, Ruth Ferreira (Associação Brasileira de Otorrinolaringologia e Cirurgia Cervicofacial, 2012)
O P300 desempenha um papel fundamental como método de avaliação e monitoramento das demências, entre elas a doença de Alzheimer. OBJETIVO: Realizar uma busca por artigos que analisaram os valores de latência e amplitude de P300 na doença de Alzheimer. MÉTODOS: Foi realizada uma busca nas seguintes bases de dados: Web of Science, PubMed/Medline, Psyc Info, Biological Abstracts e Scielo. Utilizaram-se as seguintes palavras-chave: speed of information processing, speed of processing, information processing, aged, older, elderly, older people, alzheimer dementia, alzheimer disease, Alzheimer, além de referências cruzadas dos artigos selecionados. RESULTADOS: Foram encontrados oito estudos que preencheram os critérios de inclusão adotados para o presente trabalho. Estes estudos mostraram que existe um consenso em relação ao aumento da latência de P300 de idosos com doença de Alzheimer quando comparados com idosos sem a doença. Porém, verifica-se que, com relação à amplitude de P300, ainda não há um consenso, mas, isso pode estar relacionado às diferentes variáveis metodológicas adotadas nos estudos revisados. CONCLUSÃO: Há necessidade de se padronizar as variáveis envolvidas no método de avaliação do P300 para idosos com doença de Alzheimer, para que seja possível comparar os valores de latência e amplitude de P300 dessa população.

The P300 plays a key role as a method for monitoring and evaluating dementia, including Alzheimer's disease. OBJECTIVE: The goal of this study was to search for articles which analyzed P300 latency and amplitude values in Alzheimer's disease. METHODS: We searched in the following databases: Web of Science, Pub Med, Psyc Info, Medline, Biological Abstracts and Scielo using the following keywords: speed of information processing, processing speed, information processing, aged, older, elderly, older people, alzheimer dementia, alzheimer disease, Alzheimer and cross-references of selected articles. RESULTS: We found eight studies matching the inclusion criteria. These studies showed that there is a consensus on a P300 latency increase of elderly patients with Alzheimer's disease compared with subjects without the disease. However, it appears that, with respect to the P300 amplitude, there is still no consensus; however, it may be related to different methodological variables adopted in the reviewed studies. CONCLUSION: There is a need to standardize the variables involved in P300 measurement for senior citizens with Alzheimer's disease in order to be able to compare P300 latency and amplitude values for this population.
P300 latency and amplitude in Alzheimer's disease: a systematic review
Keywords: cognição; doença de alzheimer; envelhecimento; potencial evocado p300; aging; alzheimer disease; cognition; event-related potentials; p300